Novas possibilidades para determinação do teor de biodiesel em óleo diesel para aplicação em distribuidoras de combustíveis - Sousa, Cárita Lorenza Santos (2015)
Currently in Brazil, all diesel oil available to the consumer has a minimum percentage of biodiesel required in accordance with present law, making essential the analytical control of the biodiesel content in the mix due to technical and legal order. Thus, the aim of this study was to propose the use of an inexpensive, easy to perform analytical method suitable for quantification and able to be adopted for the quality control of BX mixes in fuel distributors, which are required to ensure the correct percentage of the mixture and, unlike gas stations, have access to diesel oil and biodiesel originally used for producing the mixture BX. This is required to ensure the correct percentage of the mixture because unlike the gas stations, they have access to the diesel and biodiesel originally used for producing the mixture BX. Five different techniques for quantifying the biodiesel content were tested: points of fog and fluidity, differential scanning calorimetry, fluorescence in the ultraviolet to determine the sulfur content and specific mass at 20 °C. Diesel type A and biodiesel samples used were characterized by physicochemical parameters in accordance with present regulations. Among these techniques, only the assay of specific gravity at 20 ºC showed suitable linearity and repeatability, independent of the kind of diesel fuel used. A comparison was also performed between the results obtained with the method adopted by the ANP, which is based on infrared spectroscopy. The results showed that there is no statistical difference between the methods of FTIR and determination of density at 20 ºC, showing that this technique can be applied to quantify the biodiesel content in diesel fuel by fuel distributors.